Conceptual Metaphor Analysis of Donald Trump's Recognition of Jerusalem in Al Jazeera's News Articles - Fibrie Permata Sari; Bambang Yudi Cahyono; Aulia Apriana (Universitas Negeri Malang, 2021)
Abstract: This study investigates the conceptual metaphor of Donald Trump’s recognition of Jerusalem as the capital of Israel in Al-Jazeera’s news articles which were published online through its website. To achieve the objective of this study, the researcher referred to the general notion of metaphor and Lakoff and Johnson’s Conceptual Metaphor Theory (CMT). Using a descriptive qualitative approach, the researcher obtained 10 news articles reporting about the topic. However, 6 articles were randomly picked to be examined further. Two stages of Charteris-Black’s method (2004) namely Identification and Interpretation were adopted to examine the data. MIP were employed in the Identification stage to determine which lexical units were metaphorical. The results show that there are 4 conceptual metaphors which represent the US recognition of Jerusalem as the capital of Israel. From the results of the present study, it can be concluded that Donald Trump’s recognition of Jerusalem is conceptualized into different kinds of domain. Regarding the theoretical framework, it can also be concluded that both frameworks provide a foundation in understanding the application of metaphors in news articles. Keywords: conceptual metaphor, Donald Trump’s recognition of Jerusalem, Al-Jazeera, news articles Abstrak: Penelitian ini bertujuan untuk menyelidiki metafora konseptual tentang pengakuan Donald Trump atas kota Yerusalem sebagai ibu kota Israel pada artikel berita yang dipublikasikan oleh situs web Al-Jazeera. Beberapa teori seperti teori umum metafora dan Conceptual Metaphor Theory (CMT) dijadikan sebagai acuan untuk mencapai tujuan penelitian. Dengan menggunakan pendekatan deskriptif kualitatif, 10 artikel berita dengan topik terkait kemudian dikumpulkan sebagai data. Enam artikel berita diambil secara acak untuk dianalisis lebih dalam. Dua tahap analisis, yaitu Identification dan Interpretation dari Metode Charteris-Black (2004), dipakai untuk menganalisis data penelitian. Pada tahap Identification, prosedur MIP digunakan untuk menganalisis unit leksikal mana yang termasuk metaforik. Hasil penelitian menunjukkan bahwa ada 4 konseptual metafora yang merepresentasikan pengakuan Donald Trump atas Yerusalem sebagai ibukota dari Israel. Berdasarkan hasil penelitian, dapat disimpulkan bahwa pengakuan Donald Trump atas Yerusalem dikonseptualisasikan ke dalam domain yang berbeda-beda. Mengenai hubungannya dengan kerangka teori, teori umum metafora dan Conceptual Metaphor Theory keduanya memberikan landasan dalam memahami aplikasi metafora dalam artikel berita. Kata kunci: metafora konseptual, pengakuan Donald Trump atas Yerusalem, Al-Jazeera, artikel berita